Sistem Informasi TK Harapan Bunda Sebagai Media Promosi Berbasis Web (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
Research Method: The community and prospective parents have difficulty accessing information about TK Harapan Bunda because they often have to come directly to the school in the morning or meet the school outside of working hours. This hinders efficiency and is time-consuming for them, as well as burdening educators. Therefore, a modern solution is needed such as an official website or digital platform to facilitate access to information quickly and practically. Research Results: The purpose of implementing the system is to evaluate whether the developed system has met expectations. Through testing and implementation, the quality of the system can be assessed. Conclusion: Based on the research and implementation of the TK Harapan Bunda web-based Information System, it can be concluded that: a) The web-based information system provides easier and faster access for the community and prospective parents to obtain information about the school. b) The professionally designed website has succeeded in improving the image of TK Harapan Bunda with an attractive appearance and informative content, which promotes the school's excellent programs and achievements, thereby increasing the interest of prospective students and parental trust. c) The use of modern technology in the development of this system shows that TK Harapan Bunda is able to adapt to increasingly rapid digital developments.